Pseudomonas aeruginosa strain K and production of protease therefrom - Raja Abdul Rahman, Raja Noor Zaliha; Salleh, Abu Bakar; Basri, Mahiran; Abdul Razak, Che Nyonya; Lee, Poh Geok (2003)

(untitled)
A biologically pure strain of bacteria Pseudomonas aeruginosa strain K capable of producing protease which is tolerant to any organic solvent selected from the group consisting of 50% (v/v) benzene, n-hexane, 1-decanol, isooctane and n-hexadecane is disclosed. The strain K has an optimum growth temperature between 37?C -45 ?C and an optimum growth at pH 7. A test positive for oxidase activity, catalase activity, gelatin liquefaction, nitrate reduction, hydrogen sufide production and ?-galactotosidase (ONPG) and test negative for gram stain, indole test, methyl red, Voges-Proskauer and starch hydrolysis. It is straight rod shape Suitable nutrient medium is disclosed.